2023
DOI: 10.3390/jcm12134231
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model for the Non-Invasive Diagnosis of Endometriosis Based on Clinical Parameters

Lutz Konrad,
Lea M. Fruhmann Berger,
Veronica Maier
et al.

Abstract: Objectives: Are other pain symptoms in addition to dysmenorrhea, dyspareunia, dyschezia, dysuria, and chronic pelvic pain correlated to endometriosis and suitable for a clinical prediction model? Methods: We conducted a prospective study from 2016 to 2022, including a total of 269 women with numerous pain symptoms and other parameters. All women filled out two questionnaires and were examined by palpation and transvaginal ultrasound (TVUS). In cases of suspected deep endometriosis, magnetic resonance imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(65 reference statements)
0
1
0
1
Order By: Relevance
“…Our group recently showed that targeted taking of patientsʼ history using a patient questionnaire has a high sensitivity (90.4 %) for predicting the presence of endometriosis [25]. The pain intensity can therefore function as a discriminating parame-ter, although no conclusions can be drawn about the extent of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group recently showed that targeted taking of patientsʼ history using a patient questionnaire has a high sensitivity (90.4 %) for predicting the presence of endometriosis [25]. The pain intensity can therefore function as a discriminating parame-ter, although no conclusions can be drawn about the extent of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Unsere Arbeitsgruppe konnte kürzlich zeigen, dass durch eine gezielte Anamnese anhand eines Patientinnenfragebogens das Vorliegen einer Endometriose mit hoher Sensitivität (90,4 %) vorausgesagt werden kann [25]. Insofern kann die Schmerzintensität durchaus als diskriminierender Parameter dienen, allerdings ohne Rückschlüsse auf die Ausdehnung zuzulassen.…”
Section: Diskussionunclassified